Starfruit extract (Averrhoa bilimbi) as an alternative ingredient in the treatment of aphthous stomatitis and gingivitis - Suharja, Eliati Sri (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Stomatitis is a lesion of the oral mucosa, inner cheek, inner lip, tongue, gums, and palate. Although it is not dangerous, canker sores are very annoying. Gingivitis is inflammation of the gingival area and is the most common disease in the community. The content of starfruit (Averrhoa bilimbi) includes saponins, tannins, glucosides, and calcium, one of the best known as thrush drugs. In addition, the use of herbal plants such as star fruit (Averrhoa bilimbi) to reduce the risk of caries because this plant has antibacterial ability. Objective: This study aimed to analyze the efficacy of starfruit on the healing of aphthous stomatitis and gingivitis. Methods: the type of research used is quasi-experimental, with a pre and post-test design. The sampling technique used purposive sampling. The data collection instrument used to measure the diameter of stomatitis was using a caliper and measuring gingivitis using the WHO standard measuring instrument, namely the gingival index. Analysis of the data used was a paired sample test to compare stomatitis and gingivitis before and after the intervention. Result: the application of starfruit (Averrhoa bilimbi) showed p= 0.000 and the gingival index showed p=0.016, meaning that starfruit extract (Averrhoa bilimbi) was effective in treatment of aphthous stomatitis and gingivitis. Conclusion: starfruit extract (Averrhoa bilimbi) is effective as an alternative ingredient in the treatment of aphthous stomatitis and gingivitis.